Reformulation of Legal Protection Policies for Environmental Activists Against Criminalization in the Digital Space: Perumusan Ulang Kebijakan Perlindungan Hukum bagi Aktivis Lingkungan Hidup Terhadap Kriminalisasi di Ruang Digital - Deswat, Yoga; Yuherman, Yuherman; Fahririn, Fahririn; Nugroho, Wahyu (Mendapo: Journal of Administrative Law, 2026)
The criminalization of environmental activists through the application of the Electronic Information and Transactions Law reflects the tension between the protection of freedom of expression and the use of criminal law in the digital sphere. This study aims to analyze the application of hate speech provisions in the Daniel Tangkilisan case, evaluate the effectiveness of legal safeguards against lawsuits or criminal proceedings intended to suppress public participation in environmental matters, and formulate the direction of legal policy reform for the protection of environmental activists. This research employs normative legal research using statutory, case, and conceptual approaches. The analysis is conducted through a systematic and teleological interpretation of legislation, judicial decisions, and legal doctrines. The findings reveal divergent judicial paradigms between the Jepara District Court and the Semarang High Court in interpreting freedom of expression and public participation. The Jepara District Court adopted a formalistic approach, whereas the Semarang High Court applied a constitutional approach that recognized the protection of environmental defenders. The study further finds that the safeguards provided under the Environmental Protection and Management Law and the Supreme Court Regulation on the Adjudication of Environmental Cases remain ineffective due to the absence of procedural mechanisms within the criminal justice system. The novelty of this study lies in integrating the analysis of two judicial decisions arising from the same case with the formulation of an early-case screening model as a legal mechanism to protect public participation in the digital space. The findings contribute to the development of legal policies grounded in ecological democracy and the protection of citizens’ constitutional rights.